Case studies to illustrate good practice in the management of non-tuberculous mycobacterial pulmonary disease. (2022) - Tiberi, Simon; Lipman, Marc C.; Floto, Andres
Abstract: Pulmonary disease caused by non-tuberculous mycobacteria (NTM-PD) can be a complex condition for health care providers to manage, and delayed diagnosis and treatment failure are common. Here we present three case studies that illustrate key challenges in the diagnosis and treatment of NTM-PD, and provide guidance on these issues. In addition, we make recommendations on how the overall management of NTM-PD may be improved, through strategies such as physician education to recognise NTM-PD, and the development of multidisciplinary teams and patient-support groups.